ANCAMAN FINANSIAL DAN GAYA HIDUP SEHAT DI KALANGAN MAHASISWA KEPERAWATAN USIA REMAJA AKHIR DI DAERAH PEDESAAN JAWA TIMUR - Apriana Rahmawati; Bagus Dwi Cahyono; Evy Aristawati; Nurul Huda; Ronal Surya Aditya; Trihaningsih Puji Astuti (Poltekkes Kemenkes Semarang, 2026)
Perceived financial stability and uncertainty may impair physical and mental health during late adolescence. Yet, its association with health-promoting lifestyle among nursing students in resource-limited community settings remains underexplored. This study aimed to analyze the relationship between financial threat and health-promoting lifestyle among late adolescent nursing students. A descriptive quantitative study with a cross-sectional design was conducted in September 2025 with 69 nursing students undergoing rural community fieldwork in a rural district participated. Data were collected using two validated instruments: (1) the Financial Threat Scale (FTS), which measures subjective financial anxiety, perceived economic uncertainty, and financial burden (Cronbach’s α = 0.776), and (2) a modified 10-item Health-Promoting Lifestyle Profile II (HPLP-II), which assesses multidimensional health behaviors across six domains (Cronbach’s α = 0.850). Both continuous variables were dichotomized (low/high) based on empirically derived cut-offs (FTS ≤14 vs. ≥15; HPLP-II ≤37 vs. ≥38) to enable Chi-Square analysis, a non-parametric test appropriate for categorical data with modest sample sizes and potential non-normality. Analyses included descriptive statistics, Pearson’s correlation, and Chi-Square tests with Fisher’s Exact Test. High financial threat was reported by 40.6% (n = 28); 53.6% (n = 37) demonstrated good health-promoting lifestyle. No significant association was found either on a continuous basis, with r = 0.147 and p = 0.228, or on a categorical basis, with χ² = 0.981 and p = 0.322; Fisher's exact test, p = 0.339 meaning that students experiencing high financial threat were just as likely to maintain good health-promoting behaviors as those with low threat. although this study did not directly measure familial support, professional identity or academic scaffolding, the absence of a significant association between financial threat and health-promoting lifestyle despite high levels of perceived threat aligns with emerging literature suggesting that such culturally embedded protective mechanism may buffer the behavioral impact of financial stress in collectivist, low and middle income contexts.